2008
DOI: 10.1016/j.jpaa.2007.06.010
|View full text |Cite
|
Sign up to set email alerts
|

McCoy rings and zero-divisors

Abstract: We investigate relations between the McCoy property and other standard ring theoretic properties. For example, we prove that the McCoy property does not pass to power series rings. We also classify how the McCoy property behaves under direct products and direct sums. We prove that McCoy rings with 1 are Dedekind finite, but not necessarily Abelian. In the other direction, we prove that duo rings, and many semi-commutative rings, are McCoy. Degree variations are defined, studied, and classified. The McCoy prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…Now let R be an IFP ring, and f (x), g(x) ∈ R[x] be nonzero polynomials satisfying f (x)g(x) = 0. In this situation, Camillo and Nielsen showed that if r R [x] (f (x)) ∩ R = 0 then deg f (x) > 2 in [7,Theorem 5.5]. We here elaborate upon this theorem by finding nonzero elements in R contained in the right annihilator of f (x) when the degree of f (x) is ≤ 2.…”
Section: Annihilators Of Polynomials On Ifp Ringsmentioning
confidence: 95%
“…Now let R be an IFP ring, and f (x), g(x) ∈ R[x] be nonzero polynomials satisfying f (x)g(x) = 0. In this situation, Camillo and Nielsen showed that if r R [x] (f (x)) ∩ R = 0 then deg f (x) > 2 in [7,Theorem 5.5]. We here elaborate upon this theorem by finding nonzero elements in R contained in the right annihilator of f (x) when the degree of f (x) is ≤ 2.…”
Section: Annihilators Of Polynomials On Ifp Ringsmentioning
confidence: 95%
“…We need the following result which is a generalization of [8,Theorem 8.2] to the more general setting: Theorem 2. 27.…”
Section: Lemma 25 ([19 Theorem 44])mentioning
confidence: 99%
“…We apply the method of Camillo and Nielsen in the proof of [8,Theorem 8.2]. For every γ ∈ R * M we let I γ denote the right ideal generated by the coefficients of γ.…”
Section: Lemma 25 ([19 Theorem 44])mentioning
confidence: 99%
“…In 2006, Nielsen [15] gave an example of semi-commutative ring which is not right McCoy. The concept of a linearly McCoy ring, which properly generalizes McCoy rings and semi-commutative rings, was introduced by Camillo and Nielsen [4] . Related results on McCoy conditions can be found in [4,5,10,12,15,16,17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of a linearly McCoy ring, which properly generalizes McCoy rings and semi-commutative rings, was introduced by Camillo and Nielsen [4] . Related results on McCoy conditions can be found in [4,5,10,12,15,16,17], etc. Recently, the McCoy and the Armendariz conditions were extended to their module versions (see [3,6]).…”
Section: Introductionmentioning
confidence: 99%